2017
DOI: 10.1111/dom.13155
|View full text |Cite
|
Sign up to set email alerts
|

Impact of differing glucose‐lowering regimens on the pattern of association between glucose control and survival

Abstract: AimsTo characterize survival in relation to achieved glycated haemoglobin (HbA1c) level within alternative glucose‐lowering regimens with differing risks of hypoglycaemia.MethodsData were extracted from the UK Clinical Practice Research Datalink and the corresponding Hospital Episode Statistics. Patients with type 2 diabetes prescribed glucose‐lowering therapy in monotherapy or dual therapy with metformin between 2004 and 2013 were identified. Risk of all‐cause mortality within treatment cohorts was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…The goals of therapy should be tailored to each metabolic phenotype. It has been shown that lower HbA1c (< 7%) to be associated with increased mortality risk compared with moderate levels (≥ 7% < 8.5%) in patients using regimens that are associated with hypoglycaemia [ 139 ]. High levels of HbA1c were consistently associated with elevated mortality risk in those regimens that have a lower risk of hypoglycaemia.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The goals of therapy should be tailored to each metabolic phenotype. It has been shown that lower HbA1c (< 7%) to be associated with increased mortality risk compared with moderate levels (≥ 7% < 8.5%) in patients using regimens that are associated with hypoglycaemia [ 139 ]. High levels of HbA1c were consistently associated with elevated mortality risk in those regimens that have a lower risk of hypoglycaemia.…”
Section: Methodsmentioning
confidence: 99%
“…High levels of HbA1c were consistently associated with elevated mortality risk in those regimens that have a lower risk of hypoglycaemia. These data suggest that, in the individualisation of glycaemic targets, consideration needs to be given to the classes of glucose-lowering therapy that are being used, with less aggressive targets in those patients who are being treated with therapies associated with hypoglycaemia [ 139 ]. Goals of therapy are, therefore, depends on the metabolic phenotype of the frail older patient with diabetes (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Not only glycaemic targets, but also the choice of hypoglycaemic agent and the physical function of the individual, appear to have had an impact on the outcome. It was shown that a lower HbA1c (<7.0%) was associated with an increased mortality risk, compared with moderate levels (≥7.0% <8.5%) in patients using regimens that were associated with hypoglycaemia [54]. High levels of HbA1c were consis-tently associated with an elevated mortality risk in those regimens that had a lower risk of hypoglycaemia.…”
Section: Goals Of Therapymentioning
confidence: 99%